Pembuatan Antena Reflektor Parabola Lingkaran untuk Penerima Sinyal Televisi pada Jalur UHF - Nasrul - - (Jurnal Ilmiah Poli Rekayasa, 2018)
An antenna is a device that can receive electromagnetic waves at the receiver, and radiate electromagnetic waves on the transmitter. With the antenna we can receive information transmitted by the transmitting station through the receiver. In other words antenna helps in doing long distance connection with transmitter. In general, the antenna used to receive television signals uses many elements such as driven, reflectors, and directors. But in this study the antenna was made by using a parabolic reflector with a half-lambda driven dipole without using a director.Antenna is made there are several parameters measured as a proof of the success of the antenna. The parameters are: antenna gain, antenna impendance, VSWR (Voltage Standing Wave Ratio). The success of the antenna is also determined by the antenna's ability to receive a television signal which can also be seen by performing a direct test of the antenna.